Sumbanese’s Traditional Ecological Knowledge (TEK): Warung Hupu Liku Ritual and Ecological Ethics - Wohangara, Retang; Sanjaya, Ridwan; Setiyanto, Benny D. (Soegijapranata Catholic University, 2023)
Traditional communities have long been recognized as actors practicing nature-friendly behaviors. They are commonly deemed the champion of sustainable lifestyles. Since the 1980s, there has been a call to learn the so-called Traditional Ecological Knowledge (TEK) embraced by traditional communities. One of the reasons is that the issues of climate crises should be addressed and tackled from various corners. This article attempts to delineate a TEK, an ecological ritual practiced by the traditional community living on the island of Sumba. The ritual, called WHL (warung hupu liku, which means giving the rope tips back [to nature]), could give us an idea of how the community perceives their relationship with natural surroundings, which in turn, exposes their ecological ethics. Primary research data were collected through interviews with four experts of Sumbanese culture/environmental activists and two ritual speakers (wunang). The research reveals that WHL ritual portrays the Sumbanese’s worldview of the human-nature relationship. WHL gives an idea of the Sumbanese ecological ethics, covering reciprocity with nature, mutual respect, modesty in consumption, and sustainable use of natural resources. Because Indonesia is rich in TEK, this time-enduring knowledge and practice should be exposed as a valuable contribution to ecological discourses and policies. The discussion on Sumbanese WHL suggests that traditional and modern approaches could work in tandem to address current environmental issues.